Encapsulation of protein microfiber networks supporting pancreatic islets - Steele, Joseph A. M.; Barron, Annelise E.; Carmona, Euridice; Hallé, Jean-Pierre; Neufeld, Ronald J. (Journal of biomedical materials research. Part A, 2012)
Networks of discrete, genipin‐crosslinked gelatin microfibers enveloping pancreatic islets were incorporated within barium alginate microcapsules. This novel technique enabled encapsulation of cellular aggregates in a spherical fibrous matrix <300 μm in diameter. Microfibers were produced by vortex‐drawn extrusion within an alginate support matrix. Optimization culminated in a hydrated fiber diameter of 22.3 ± 0.4 μm, a significant reduction relative to that available through current gelatin microfiber spinning techniques, while making the process more reliable and less labor intensive. Microfibers were encapsulated at 40 vol % within 294 ± 4 μm 1.6% barium alginate microparticles by electrostatic‐mediated dropwise extrusion. Pancreatic islets extracted from Sprague Dawley rats were encapsulated within the microparticles and analyzed over 21 days. Acridine orange and propidium iodide fluorescent viability staining and light microscopy indicated a significant increase in viability for islets within the fiber‐embedded particles relative to fiber‐free controls at days 7, 14, and 21. The fiber‐embedded system also promoted cellular aggregate cohesion, reducing the incidence of dispersed islet morphologies within the capsules from 31 to 8% at day 21. Further enquiry into benefits of islet encapsulation within a protein fiber network will be the subject of future investigation. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 100A:3384–3391, 2012.